Goat milk free fatty acid characterization during conventional and ohmic heating pasteurization - Pereira, Ricardo (2008)
The disruption of the milk fat globule membrane can lead to an excessive accumulation of free fatty acids in milk, which is frequently associated with the appearance of rancid flavors. Solid-phase microextraction and gas chromatography techniques have been shown to be useful tools in the quantification of individual free fatty acids in dairy products providing enough sensitivity to detect levels of rancidity in milk. Therefore, the aim of this study was to characterize the short-chain and medium-chain free fatty acid profile in i) raw untreated goat milk; ii) raw goat milk passing through pumps and heating units (plate-and-frame heat exchanger and ohmic heater); and iii) processed goat milk by conventional and ohmic pasteurization to determine the influence of each treatment in the final quality of the milk. Multivariate statistical analysis has shown that the treatments studied were not responsible for the variability found on free fatty acid contents. In particular, it was possible to conclude that ohmic pasteurization at 72°C for 15 s did not promote an extended modification of free fatty acid contents in goat milk when compared with that of conventional pasteurization. Furthermore, principal component analysis showed that the capric acid can be used to discriminate goat’s milk with different free fatty acid concentrations. Hierarchical cluster analysis showed evidence of the existence of correlations between contents of short and medium chain free fatty acids in goat milk.